Analisis Pengaruh Modal Kerja Terhadap Current Rasio Pada PT. Telkom Indonesia, Tbk Dan PT. Xl Axiata, Tbk - Devita Nurhayati; Nurhayati Nurhayati; Puji Muniarty (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the influence of working capital on the current ratio at PT. Telkom Indonesia, Tbk and PT. XL Axiata, Tbk. This type of research is associative. The research instrument used is a list of tables containing data on current assets, current liabilities and current liabilities at PT. Telkom Indonesia Tbk, PT. XL Axiata, Tbk for 10 years, namely from 2013 to 2022. The population in this activity is in the form of financial data including: financial reports at PT. Telkom Indonesia, Tbk and PT. XL Axiata, Tbk from 2000-2022, namely for 22 years. The sampling technique used by researchers in this research is purposive sampling technique. The number of research samples for the last 10 years from 2013 to 2022 at PT. Telkom Indonesia, Tbk and PT. XL Axiata, Tbk. Data collection techniques in this research are documentation and literature study. Data analysis techniques use simple linear regression, correlation coefficient, determination test and t test. The research results show that there is a significant influence between working capital and the current ratio at PT. Telkom Indonesia, Tbk, PT. XL Axiata, Tbk.